1997
DOI: 10.1111/j.1600-0536.1997.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of previous allergic contact dermatitis for elicitation of delayed hypersensitivity to nickel

Abstract: Several factors, such as amount of allergen, vehicle, anatomic site, immunologic status and previous eczema, may influence delayed hypersensitivity reactions. In an extended model, we have studied the significance of previous allergic contact dermatitis for elicitation of delayed hypersensitivity to nickel in 25 nickel-allergic females. On 3 occasions, 8, 4 and 1 months before the final challenge patch testing, an experimental allergic contact dermatitis from nickel was induced on the lower back. At the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 12 publications
5
54
0
Order By: Relevance
“…When the number of negative and/or doubtful reactions was followed by at least the same number of positive reactions, the lowest positive reaction was considered the MEC (12). If negative or doubtful reactions at 2.0% and 1.3% were followed by a positive reaction at 1.0% (as in subject 3), the latter was registered as the MEC.…”
Section: Statisticsmentioning
confidence: 99%
“…When the number of negative and/or doubtful reactions was followed by at least the same number of positive reactions, the lowest positive reaction was considered the MEC (12). If negative or doubtful reactions at 2.0% and 1.3% were followed by a positive reaction at 1.0% (as in subject 3), the latter was registered as the MEC.…”
Section: Statisticsmentioning
confidence: 99%
“…We found signi¢cantly higher test reactivity in areas where there had been nickel contact dermatitis previously, compared with areas where there had never been nickel eczema before. We also found that the shorter the time interval between previous eczema and topical re-exposure, the stronger the reaction (1). Whether this increased re-test reactivity is allergen-speci¢c or also exists after allergic contact dermatitis from other sensitizers is unclear.…”
mentioning
confidence: 73%
“…With regard to SLS, the test occlusion time used was 24 h, the time most frequently used in studies of irritant skin reactions (8). The same test system was used as in a previous study (1) to produce an experimental eczema as homogeneous as possible. In order to provoke the same degree of epidermal in£ammation from the experimentally induced allergic and irritant contact dermatitis, the patients were patch tested with a serial dilution of nickel sulfate, cobalt chloride, and SLS immediately before the provocation.…”
Section: On the Designmentioning
confidence: 99%
“…For example, there was no effect on the nickel reactivity when SLS was administered simultaneously with the allergen by an open application procedure on normal forearm skin (Menne´and Calvin 1993). However, the nickel reactivity was decreased when contact dermatitis was provoked by SLS 1 month prior to a nickel closedchallenge patch test on the compromised skin area on the back (Hindse´n et al 1997). In contrast, the nickel reactivity was increased on forearm skin if SLS dermatitis was provoked by immersion in SLS solution a few hours prior to the nickel challenge (Allenby and Basketter 1993).…”
Section: Dose-response Relationshipmentioning
confidence: 92%